2005
DOI: 10.1097/01.sap.0000154871.97860.ea
|View full text |Cite
|
Sign up to set email alerts
|

Paraumbilical Perforator-Based Pedicled Abdominal Flap for Extensive Soft-Tissue Deficiencies of the Forearm and Hand

Abstract: A new paraumbilical-based pedicled abdominal flap was used in 11 patients with extensive soft-tissue defects of the forearm and hand. With a relatively narrow pedicle, large flaps up to 5- x 14-cm can be raised. Another advantage of this flap is the comfortable position of the hand and forearm for the patient. The main disadvantage is the conspicuous abdominal scars like the other pedicled abdominal flaps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 6 publications
0
34
2
Order By: Relevance
“…This is in difference with previous studies done by Yilmaz et al,19 wherein majority of the patients were females which formed 72.7% of that respective study. Male preponderance in our study is because of the fact that males are more exposed to the upper limb trauma in our scenario.…”
Section: Resultscontrasting
confidence: 56%
“…This is in difference with previous studies done by Yilmaz et al,19 wherein majority of the patients were females which formed 72.7% of that respective study. Male preponderance in our study is because of the fact that males are more exposed to the upper limb trauma in our scenario.…”
Section: Resultscontrasting
confidence: 56%
“…In study done in 11 patients by Sarper Yilmer studied for extensive soft tissue defects of forearm and hand showed that a relatively narrow pedicle, large flap up to 5x14 cm can be raised. 6 Comfortable position of the hand and forearm was also observed.…”
Section: Discussionmentioning
confidence: 91%
“…It is the superior oblique design that allows flap harvests of up to 30 cm in length, as opposed to the 14 cm in length described by Yilmaz, using the inferior oblique design. 9 Although these authors describe reconstructing 7 patients with forearm defects, they do not specify proximal or distal forearm location, and the pictures portray only distal forearm wounds. 9 On average, the flap is 28 cm in length and 8 cm in width, giving it a 3:1 length-to-width ratio.…”
Section: Discussionmentioning
confidence: 97%
“…9,10,[12][13][14] The different flap names reflect the skin design, feeding axial vessel, and/or use of muscle, as in the oblique rectus abdominis flap 14,15 or the extended deep inferior epigastric flap, 12,16 each used in reconstruction of various anatomic defects such as the perineum, groin, or lower extremity. Skin paddles can be oriented from the umbilicus laterally in one of several directions, similar to the spokes of a wheel, paralleling vascular anastomoses within the subdermal plexus between the dominant paraumbilical perforators and more peripheral abdominal wall or intercostal vessels.…”
mentioning
confidence: 99%